Avaliação histopatológica da movimentação dentária induzida em dentes submetidos à luxação lateral experimental - CANTANHEDE, Luana Martins (2017)
Dental trauma affects some patients seeking orthodontic treatment. The dental movement for these cases can cause worse prognoses, because the forces will affect the same tissues that are on the trauma repair. The purpose of this study was to evaluate microscopically the biological events of induced tooth movement 15 and 30 days after experimental lateral luxation. The sample consisted of 30 male rats and according to the splitmouth technique were divided into six groups, each group with 10 first maxillary molars . The control group (GC ) was not submitted to dental trauma (TD) or induced tooth movement (ITM), the Control Movement Group (GCM), ITM was only performed in the Trauma Control Groups 15 and 30 days (TG C15 and TG C30), TD was performed, followed by repositioning, evaluated after 22 and 37 days respectively, in Trauma and Movement Groups 15 and 30 days (TG M15 and TG M30), the animals suffered TD and, respectively, after 15 and 30 days, were submitted to ITM for seven days for further evaluation. Histological slides were produced whose qualitative analyzes occurred in the mesial side of the distal root, in the distal side of the mesial root and in the furca on the first maxillary molar. Semiquantitative analysis of the region was also performed using the Freeman-Halton extension of Fisher's exact test. Chronic Inflammatory infiltrate Characteristics was exacerbated in the distal side of the furca in the TG M15 group were found, and resorption characteristics were found in the TG M30 group. Semiquantitative analysis demonstrated that the most evident scores of inflammatory infiltrate were concentrated in the distal region of the furca of the TG M15 group and the resorption characteristics were more evident in the central region of the furca. It was conclude that tooth movement 15 days after trauma may result in more exuberant histological alterations in relation to inflammatory infiltrate and movement after 30 days can lead to more severe root resorption.